Multiple sclerosis in research workers studying swayback in lambs: an updated report. Issue 9 (September 1985) - Dean, G; McDougall, E I; Elian, M
Abstract : Four out of seven research workers into swayback disease, a neurological disease of lambs, developed symptoms and signs of multiple sclerosis, and were reported in 1947. A further worker later joined the group. All of the original seven have died and two at necropsy had multiple areas of demyelination in the brain and spinal cord. The chance of four or more out of a random group of eight men developing multiple sclerosis is about one in a thousand million. Multiple sclerosis has not occurred in other workers on swayback disease elsewhere.